Combine proper exercise and regular taking antihypertensive medicine was better to lower diastolic blood pressure among diastolic prehypertensive and hypertensive subjects (Faculty of Medicine Universitas Indonesia, 2010)
Aim To prove that proper exercise and taking antihypertensive medicine may reduce diastolic blood pressure (DBP) by ≥ 5 mmHg. Method A quasi-experimentation study was done on employees of a government bureau in Jakarta, for 8 weeks from March to August 2008. All prehypertensive and hypertensive subjects were detected through a survey prior to the quasi-experimentation study. A talk was given at the beginning of the quasi-experimentation study, and weekly counseling sessions on exercise, taking medications, and other related topics continued for 8 weeks. Cox regression was used for calculating relative risk. Results A total 1,016 employees out of 1,300 were involved in this blood pressure survey. Of these, 318 subjects had a DBP of 80 mmHg or more. Out of 120 subjects who voluntarily participated, 104 subjects completed the quasi-experimentation study. Compared to those who did not exercise properly and did not take antihypertensive medicines, subjects who did exercise properly and took medicines regularly had a lower diastolic blood pressure DBP ≥5 mmHg by more than 12-fold [adjusted relative risk (RRa) = 12.32; 95% confidence interval (CI) = 0,65-234,54; P = 0.095. However subjects who exercised properly or took antyhypertensive medicines irregularly were found to lower their DBP ≥5 mmHg by almost 11 fold [adjusted relative risk (RRa) = 10.94; 95% confidence interval (CI) = 2.04-58.74]; P = 0.005. Subjects with DBP = 90-99mmHg had a decrease of DBP ≥5 mmHg 4.8 fold (RRa = 4.75; 95% CI = 1.19-18.65) compared to those with DBP = 80-89mmHg. Compared to the normal subjects, the obese, resting pulse rate bradycardia, and high average pulse pressure subjects had less probability of lowering DBP â¥ 5mmHg, by 87%, 90%, and 65%, respectively. Conclusion Combine proper exercise and taking antihypertensive medicine was reduce DBP by â¥5 mmHg among DBP (pre-) hypertensive subjects. The obese, bradycardia, or high pulse pressure subjects failed to lowering their DBP ≥5 mmHg by proper exercise and taking antihypertensive medicine. (Med J Indones 2009;19:191-8)